2020
DOI: 10.1101/2020.11.24.20238238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of a multi-faceted Rapid Response System re-design on repeat calling of the Rapid Response Team

Abstract: BackgroundRepeat Rapid Response Team (RRT) calls are associated with increased mortality risk to patients and pose a resource burden to organisations. Use of Non-Technical Skills (NTS) at calls has the potential to reduce potentially preventable repeat calling. NTS are usually improved through training, however this consumes time and financial resources. Modifications to the Rapid Response System (RRS) that promote use of NTS are worth exploring as a cost-effective alternative.MethodsA pre-post observational s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recent studies have suggested that proactive resuscitation models may prevent adverse events, disseminate expertise, provide support to novice staff, and reveal quality improvement opportunities. 2 Initiatives such as capitation, pay-for-performance, value-based purchasing, and quality measure compliance affect resource allocation; therefore, innovative solutions are needed to address complexity of care, cost containment, and staffing constraints. 3 This article describes the staged restructure of a consultative ICU rapid response nurse (RRN) to a dedicated 24/7 RRN model of care in a quaternary academic medical center in the southern United States.…”
mentioning
confidence: 99%
“…Recent studies have suggested that proactive resuscitation models may prevent adverse events, disseminate expertise, provide support to novice staff, and reveal quality improvement opportunities. 2 Initiatives such as capitation, pay-for-performance, value-based purchasing, and quality measure compliance affect resource allocation; therefore, innovative solutions are needed to address complexity of care, cost containment, and staffing constraints. 3 This article describes the staged restructure of a consultative ICU rapid response nurse (RRN) to a dedicated 24/7 RRN model of care in a quaternary academic medical center in the southern United States.…”
mentioning
confidence: 99%